AN ATTEMPT TO CONSERVE A VULNERABLE TREE SPECIES OF Santalum album L. THROUGH MICROPROPAGATION - Gurusamy, Manikandan; Charlie, Karolinsobina; Palanisamy, Kalaimathi; Chelladurai, Divya; Katerere, David R (Association of Indonesian Forestry and Environment Researchers and Technicians, 2024)
A rare kind of tropical plant in the Santalaceae family is Santalum album. The active ingredient in S. album, santalol, is also referred to as sandalwood oil and is highly prized in the fragrance business for its fixative qualities and pleasant, enduring scent. Out of all the species in the genus Santalum, S. album has the greatest oil concentration (about 6%). The wild plants are overharvested for their wood, which is used to make santalol, as well as for other uses including woodcarving and traditional medicine. S. album is an easily hurt plant. Thus, the creation of an in vitro mass propagation protocol for this valuable species is necessary in order to generate homozygous clones with large yields for the establishment of sandalwood plantations. In this study, a full-strength MS medium supplemented with varying concentrations of BAP and Kn (0.5-2.5 mg/l) was used to cultivate the shoot tip and intermodal portions of S. album that were collected from the wild. The maximum shoot development (4.50±0.50) occurred at a BAP concentration of 1.5 mg/l. IBA and IAA were added to the rooting medium along with the developing shoots. IBA (2.0 mg/l) had the highest mean number of roots (4.90±0.25) and root length (5.75±0.47 cm). Shoots that had been successfully rooted were moved to the field to harden. According to the current study, MS medium with 1.5 mg/l of BAP and 2.0 mg/l of IBA is an appropriate technique for micropropagating and conserving S. album is fragile tree species.